Huffman Coding Technique for Image Compression - Shaikh, A.A.; Gadekar, P.P. (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
Image compression is one of the most important steps in image transmission and storage. “A picture is worth more than thousand words “is a common saying. Images play an indispensable role in representing vitalin formation and needs to be saved for further use or can be transmitted over a medium. In order to have efficient utilization of disk space and transmission rate, images need to be compressed. Image compression is the technique of reducing the file size of a image without compromising with the image quality at acceptable level. Image compression is been used from a long time and many algorithms have been devised. In this paper we have converted an image into an array using Delphi image control tool. An algorithm is created in Delphi to implement Huffman coding method that removes redundant codes from the image and compresses a BMP image file (especially gray scale image) and it is successfully reconstructed. This reconstructed image is an exact representation of the original because it is loss less compression technique.